Glycinergic transmission modulates GABAergic inhibition in the avian auditory pathway - Fischl, Matthew J.; Burger, R. Michael (Frontiers in Neural Circuits, 2014)
For all neurons, a proper balance of synaptic excitation and inhibition is crucial to effect computational precision. Achievement of this balance is remarkable when one considers factors that modulate synaptic strength operate on multiple overlapping time scales and affect both pre- and postsynaptic elements. Recent studies have shown that inhibitory transmitters, glycine and GABA, are co-released in auditory nuclei involved in the computation of interaural time disparities (ITDs), a cue used to process sound source location. The co-release expressed at these synapses is heavily activity dependent, and generally occurs when input rates are high. This circuitry, in both birds and mammals, relies on inhibitory input to maintain the temporal precision necessary for ITD encoding. Studies of co-release in other brain regions suggest that GABA and glycine receptors (GlyRs) interact via cross-suppressive modulation of receptor conductance. We performed in vitro whole-cell recordings in several nuclei of the chicken brainstem auditory circuit to assess whether this cross-suppressive phenomenon was evident in the avian brainstem. We evaluated the effect of pressure-puff applied glycine on synaptically evoked inhibitory currents in nucleus magnocellularis (NM) and the superior olivary nucleus (SON). Glycine pre-application reduced the amplitude of inhibitory postsynaptic currents evoked during a 100Hz train stimulus in both nuclei. This apparent glycinergic modulation was blocked in the presence of strychnine. Further experiments showed that this modulation did not depend on postsynaptic biochemical interactions such as phosphatase activity, or direct interactions between GABA and glycine receptor proteins. Rather, voltage clamp experiments in which we manipulated Cl- flux during agonist application suggest that activation of one receptor will modulate the conductance of the other via local changes in Cl- ion concentration within microdomains of the postsynaptic membrane.